Monitoring the effect of perioperative nutritional care on body composition and functional status in patients with carcinoma of gastrointestinal and hepatobiliary system and pancreas - Gyergyek, Andrej (Radiology and oncology (Ljubljana), 2023)
Background. The significance of nutritional care in the management of cancer, particularly in the surgical treatment of abdominal cancer, is increasingly acknowledged. Body composition analysis, such as the Bioelectric impedance assay (BIA), and functional tests, e.g., handgrip strength, are used when assessing nutritional status alongside general and nutritional history, clinical examination, and laboratory tests. The primary approach in nutritional care is individually adjusted nutritional counselling and the use of medical nutrition, especially oral nutritional supplements. The aim of the study was to investigate the effects of perioperative nutritional care on body composition and functional status in patients with carcinoma of the gastrointestinal tract, hepatobiliary system, and pancreas. Patients and methods. 47 patients were included, 27 received preoperative and postoperative nutritional counselling and oral nutritional supplements (Group 1), while 20, due to surgical or organisational reasons, received nutritional care only postoperatively (Group 2). The effect of nutritional therapy was measured with bioimpedance body composition and handgrip measurements. Results. Group 2 had a higher average Nutritional Risk Screening (NRS) 2002 score upon enrolment (3 vs. 2 points); however, there was no difference when malnutrition was assessed using Global Leadership in Malnutrition (GLIM) criteria. There was a relative increase in lean body mass and fat-free mass index (FFMI) 7 days after surgery in group 1 (+4,2% vs. -2,1% in group 2). There was no difference in handgrip strength. Conclusions. Our results indicate that combined preoperative and postoperative nutritional care is superior to only postoperative nutritional care. It seems to prevent statistically significant lean mass loss 7 days after surgery but not after 14 days or 4 weeks.
Keywords: abdominal cancer; body composition; nutritional status; rak trebuha; stanje prehranjenosti; telesna sestava